Design of a demestic-producing astronal-level low-voltage pulse power supply - Li Shuanggang; Xu Huan; Gao Zheng (Dianzi Jishu Yingyong)
Synthetic Aperture Radar (SAR) is an active earth observation system that can observe the earth 24/7. Pulse power supply is an important component of SAR operation. This article proposes a design method for a nationally produced aerospace grade high-efficiency SAR pulse power supply, with an input voltage range of 78 V~110 V, suitable for the requirements of a 100 V wide input bus on board. It has the characteristics of small size, high power density, and low input reflection current ripple. The load pulse repetition frequency covers the range of 500 Hz and above, and adopts nationally produced and aerospace grade devices.